Pilot educational program to enhance empowering patient education of school-age children with diabetes - Kelo M; Eriksson E; Eriksson I (Tehran University of Medical Sciences, Endocrinology and Metabolism Research Center, BioMed Central, 2026)
Background
Nurses have a crucial role in patient education of children with type 1 diabetes, but they often exhibit lack of knowledge of the patient education process. This study aimed to describe an educational program to enhance empowering patient education process for the blood glucose monitoring education of school-age children and nurses’ perceptions of using empowering techniques.
Methods
An empowering patient education process for the diabetes education of school-age children was developed. The researcher collected nurse’s perceptions of managing the educational program by semi-structured interviews. Ten nurses carried out the diabetes education, and 8 of them participated in the interview. Three nurses implemented the diabetes education twice and were interviewed twice. The data consisted of 11 descriptions of the blood glucose monitoring education. The interviewer analyzed the data deductively and inductively by content analysis.
Results
Nurses described successful managing of the empowering patient education process. The need assessment consisted of using multiple methods and clarifying the capabilities and challenges of children and their parents. Planning manifested itself in adequate preparation and multiple objectives stated together with the family. Implementation comprised the relevant content, and the use of suitable teaching materials and methods. Evaluation was performed with various methods and documented accurately. Nurses also faced some challenges related to management and leadership, ambivalence with traditional and empowering patient education, and families’ overall situation.
Conclusion
An example of developing evidence-based patient education program is presented, but besides education other factors supporting changes in work practices should be considered in further development.